The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1016/s2214-109x(16)30200-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Russian-backbone live attenuated influenza vaccine among young children in Bangladesh: a randomised, double-blind, placebo-controlled trial

Abstract: SummaryBackgroundThe rates of influenza illness and associated complications are high among children in Bangladesh. We assessed the clinical efficacy and safety of a Russian-backbone live attenuated influenza vaccine (LAIV) at two field sites in Bangladesh.MethodsBetween Feb 27 and April 9, 2013, children aged 2–4 years in urban Kamalapur and rural Matlab, Bangladesh, were randomly assigned in a 2:1 ratio, according to a computer-generated schedule, to receive one intranasal dose of LAIV or placebo. After vacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 18 publications
4
42
1
1
Order By: Relevance
“…The absence of efficacy against strain-matched, laboratory-confirmed symptomatic influenza illness in this study contrasts with the findings of a similar study conducted in the same season with a single dose of Nasovac-S among children aged 2–4 years in Bangladesh 13 . In Bangladesh, H1N1pdm09 and H3N2 were the predominant strains, with attack rates of 3·6% and 12·3% in the placebo group, respectively, and vaccine efficacy of 50·0% (95% CI 9·2–72·5) against H1N1pdm09 and 60·4% (44·8–71·6) against H3N2.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The absence of efficacy against strain-matched, laboratory-confirmed symptomatic influenza illness in this study contrasts with the findings of a similar study conducted in the same season with a single dose of Nasovac-S among children aged 2–4 years in Bangladesh 13 . In Bangladesh, H1N1pdm09 and H3N2 were the predominant strains, with attack rates of 3·6% and 12·3% in the placebo group, respectively, and vaccine efficacy of 50·0% (95% CI 9·2–72·5) against H1N1pdm09 and 60·4% (44·8–71·6) against H3N2.…”
Section: Discussioncontrasting
confidence: 99%
“…Local symptoms, including nasal congestion, runny nose, and cough, were common among both vaccine and placebo recipients, with no imbalances between groups. These safety results are similar to those reported in Bangladesh during both a phase 2 study and the aforementioned efficacy trial there 13, 35. In view of the association of wheezing and admissions to hospital noted among children younger than 2 years who were vaccinated with FluMist, 36 we carefully monitored participants for wheezing illness using a standardised definition.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…However, moderate protection was observed to the H1N1 strain in Europe, with 41.5% vaccine effectiveness in the UK and 47.9% in Finland, although remaining lower than IIV . A study in Senegal found that LAIV failed to protect against H1N1pdm09 in young children, whereas protection was found in a similar study in Bangladesh . The reason for these differences is currently unknown but could be due to the vaccines were being based on different backbones, or the population's exposure history .…”
Section: Introductionmentioning
confidence: 99%
“…33 LAIV has been highlighted as a particularly valuable technology given that the straightforward, high-yield manufacturing process and needle-free administration are more transferable to low-and middle-income countries and advantageous for pandemic surge production. 34 There are very few studies of LAIV in such populations but two recent RCTs assessed efficacy of "Leningrad" LAIV in Senegal 35 and Bangladesh 36 . Surprisingly, the results from these two studies are very different, with no efficacy demonstrated in Senegal, but 41% efficacy in Bangladesh ( Table 2).…”
Section: Introductionmentioning
confidence: 99%